High mass resolution, spatial metabolite mapping enhances the current plant gene and pathway discovery toolbox. Issue 6 (13th August 2020) - Dong, Yonghui; Sonawane, Prashant; Cohen, Hagai; Polturak, Guy; Feldberg, Liron; Avivi, Shelly Hen; Rogachev, Ilana; Aharoni, Asaph
Summary: Understanding when and where metabolites accumulate provides important cues to the gene function. Mass spectrometry imaging (MSI) enables in situ temporal and spatial measurement of a large assortment of metabolites, providing mapping information regarding their cellular distribution. To describe the current state and technical advances using MSI in plant sciences, we employed MSI to demonstrate its significant contribution to the study of plant specialised metabolism. We show that coupling MSI with: (1) RNA interference (RNAi), (2) virus induced gene silencing (VIGS), (3) agroinfiltration or (4) samples derived from plant natural variation provides great opportunities to understand the accurate gene–metabolite relationship and discover novel gene‐associated metabolites. This was exemplified in three plant species (i.e. tomato, tobacco and wheat) by mapping the distribution of metabolites possessing a range of polarities. In particular, we demonstrated that MSI is able to spatially map an entire metabolic pathway, including intermediates and final products, in the intricate biosynthetic route to tomato fruit steroidal glycoalkaloids. We therefore envisage MSI as a key component of the metabolome analysis arsenal employed in plant gene discovery strategies.